Using Metaphors to Explain Molecular Testing to Cancer Patients. (20th February 2017) - Pinheiro, Ana P.M.; Pocock, Rachel H.; Dixon, Margie D.; Shaib, Walid L.; Ramalingam, Suresh S.; Pentz, Rebecca D.
Abstract : Background: Molecular testing to identify targetable molecular alterations is routine practice for several types of cancer. Explaining the underlying molecular concepts can be difficult, and metaphors historically have been used in medicine to provide a common language between physicians and patients. Although previous studies have highlighted the use and effectiveness of metaphors to help explain germline genetic concepts to the general public, this study is the first to describe the use of metaphors to explain molecular testing to cancer patients in the clinical setting. Methods: Oncologist‐patient conversations about molecular testing were recorded, transcribed verbatim, and coded. If a metaphor was used, patients were asked to explain it and assess its helpfulness. Results: Sixty‐six patients participated. Nine oncologists used metaphors to describe molecular testing; 25 of 66 (38%) participants heard a metaphor, 13 of 25 (52%) were questioned, 11 of 13 (85%) demonstrated understanding and reported the metaphor as being useful. Seventeen metaphors (bus driver, boss, switch, battery, circuit, broken light switch, gas pedal, key turning off an engine, key opening a lock, food for growth, satellite and antenna, interstate, alternate circuit, traffic jam, blueprint, room names, Florida citrus) were used to explain eight molecular testing terms (driver mutations, targeted therapy, hormones, receptors, resistance, exon specificity, genes, and cancer signatures). Conclusion: Because metaphors have proven to be a useful communication tool in other settings, these 17 metaphors may be useful for oncologists to adapt to their own setting to explain molecular testing terms. Abstract : This study described oncologists' use of metaphors to explain molecular testing to cancer patients in the clinical setting. The 17 metaphors identified here may be useful for oncologists to adapt to their own setting to explain molecular testing terms.